FIGURATIVE LANGUAGE IN SIMPLE PLAN’S ALBUM NO PADS, NO HELMETS … JUST A BALLS: SEMANTICS AND SEMIOTICS STUDY - Rendo, Antonius; Hendar (Lembaga Penelitian Universitas Pasundan, 2025)
This article purposed to conduct a comprehensive analysis of figurative language found in the lyrics of Simple Plan's album